HORIZONTAL DISTRIBUTION OF DINOFLAGELLATE CYSTS IN SURFACE SEDIMENTS OF JAKARTA BAY: SOME PRELIMINARY RESULTS - Sidharta, Boy Rahardjo; Panggabean, M. G. Lily; Mizushima, Koichiro (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
Ten surface sediment samples were collected from Jakarta Bay to study the horizontal distribution of dinoflagellate resting cysts in this area. Overall results had shown unique species composition and diversity of dinoflagellate cyst assemblages. However, dinoflagellate cysts found in this preliminary research were sparse and relatively low in term of species number and concentrations. Twenty cyst morphophites were identified in this research, within which ten cysts belong to autotrophic and another ten belong to heterotrophic species. Protoperidinium cysts were the most diversified group, predominating in almost the sampling locations. The cysts identified were generally characterized by species belonged to three orders namely Gonyaulacales, Gymnodiniales, and Peridiniales. Only one dinoflagellate cyst found that was belonged to the toxic and harmful algal bloom (HAB) member species, i.e. Gymnodinium catenatum.